Creating Well-Being: Increased Creativity and proNGF Decrease following Quadrato Motor Training. (7th June 2015) - Venditti, Sabrina; Verdone, Loredana; Pesce, Caterina; Tocci, Nicoletta; Caserta, Micaela; Ben-Soussan, Tal Dotan
Abstract : Mind-body practices (MBP) are known to induce electrophysiological and morphological changes, whereas reports related to changes of neurotrophins are surprisingly scarce. Consequently, in the current paper, we focused on the Quadrato motor training (QMT), a newly developed whole-body movement-based MBP, which has been reported to enhance creativity. Here we report the effects of 4 weeks of daily QMT on creativity and proNGF level in two interrelated studies. In Study A, we examined the effects of QMT compared with a walking training (WT) in healthy adults, utilizing the alternate uses task. In contrast with the WT, QMT resulted in increased creativity. In addition, the change in creativity negatively correlated with the change in proNGF levels. In Study B, we examined QMT effects on creativity and additional metacognitive functions in children, using a nonintervention group as control. Similar to Study A, following QMT, we found a negative correlation of proNGF with creativity, as well as working memory updating and planning ability. Together, the current results point to the relationship between increased creativity and decreased proNGF following MBP. Thus, the current research emphasizes the importance of widening the scope of examination of " MBP in motion " in relation to metacognition and well-being.